Fluid and Drug Administration Procedure Animal Model in Biomedical Research - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Drugs, vaccines, injectable anesthetics or other agents are to be administered, one or more of several different routes may be selected. The routes selected are governed by the nature of the agent being administered, the animal, the purpose of the administration and other factors.